2023
DOI: 10.1039/d2md00352j
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine based dual binding site aromatase (CYP19A1) inhibitors

Abstract: Aromatase (CYP19A1) inhibitors are the mainstay therapeutics for the treatment of hormone dependant breast cancer, which accounts for approximately 70% of all breast cancer cases. However, increased resistance to the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Computational studies of pyridine derivatives identified an alternative access channel lined by Phe221, Gln225, Trp224, and Leu477. This allows further insight into the interactions between non-steroidal aromatase inhibitors and their molecular target [ 48 ].…”
Section: Aromatase Inhibitorsmentioning
confidence: 99%
“…Computational studies of pyridine derivatives identified an alternative access channel lined by Phe221, Gln225, Trp224, and Leu477. This allows further insight into the interactions between non-steroidal aromatase inhibitors and their molecular target [ 48 ].…”
Section: Aromatase Inhibitorsmentioning
confidence: 99%